RETRACTED: Review article: The impact of algorithmic advancement on production and its sales - Malsagov Bekhan; Vassunova Yulia; Amirova Elmira (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001